Improving working conditions in platform work. A comment about the agreement reached on the European directive - Di Cataldo, Luigi (Italian Labour Law e-Journal, 2024)
Platform work represents a new form of non-standard work without recognition by European labour law. In recent years, the issue of improving working conditions in platform work has been at the heart of political and academic debate. On 11th March 2024, the employment and social affairs ministers of the EU Member States endorsed the agreement reached with the European Parliament on the Commission’s proposed directive on platform work. The directive tackles situations of wrong classification of employment status, introducing a rebuttable legal presumption and reducing the burden of proof on persons performing platform work. In addition, the directive introduces the first EU rules to regulate algorithmic management in the workplace. This paper traces the positions advocated by the European institutions in defining the strategy for improving working conditions within digital platforms and offers an extended analysis of the final text of the directive that has just been approved.